Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Gamifikasi untuk Pembelajaran Cerpen di SMK Madani Marindal I - Febriyani Ardila; Rika Kartika; Amaluddin Amaluddin (Education & Learning, 2025)
This study aimed to develop and evaluate the feasibility of Lembar Kerja Peserta Didik (Student Worksheet) assisted by gamification in short story learning for class XI students of SMK Madani Marindal I. The research employed a Research and Development (Penelitian dan Pengembangan) method using the Borg and Gall development model, which consisted of seven stages: research and data collection, planning, product draft development, initial field trials, initial product refinement, field trials, and final product refinement. The participants were 20 students from class XI Teknik Komputer dan Jaringan (Computer and Network Engineering). Data were collected through observation, interviews, and questionnaires. Validation results demonstrated that the developed Lembar Kerja Peserta Didik had high feasibility. Material Expert I assessed it as “Feasible” (84%), while Material Expert II rated it “Feasible” (80%). Media Expert I categorized it as “Very Feasible” (92%), and Media Expert II rated it “Very Feasible” (90%). The response from the Indonesian language teacher indicated a “Very Feasible” level (98%), while students’ responses showed a “Feasible” category (79.2%). The product trial also proved its effectiveness in enhancing learning outcomes, with students’ achievement increasing from 65% to 88% after implementation, showing a 23% improvement. Overall, the results indicate that Lembar Kerja Peserta Didik based on gamification is highly feasible and effective for short story learning in vocational high schools.